ANALYSIS OF THE RELATIONSHIP BETWEEN THE PROVISION OF BASIC INFRASTRUCTURE AND THE QUALITY OF THE ENVIRONMENT IN INFORMAL AREAS (CASE STUDY: RW 13 AND RW 14, SADANG SERANG VILLAGE, BANDUNG CITY) - Afrian, Laura
The high population density due to urbanization causes the demand for land for settlements to be disproportionate to the availability of existing land, resulting in the formation of slum settlements. Slum settlements are informal areas that are unfit for habitation which are characterized by basic infrastructure including environmental roads, clean water supply, environmental drainage, waste water management and waste management that do not meet standards (Regulation of the Minister of PUPR of the Republic of Indonesia Number 02/PRT/M/2016 concerning Improving the Quality of Slum Housing and Slum Settlements). The limitations of basic infrastructure in meeting the needs of an ever-increasing population, especially in areas with relatively high population density, will affect the quality of the living environment in these areas, such as a decline in the quality of hygiene which is characterized by the emergence of various kinds of diseases, high levels of air pollution, flooding in urban areas, decline in people's productivity due to stress, and so on. Therefore, treatment is needed as soon as possible, one of which is through the provision of quality basic infrastructure capable of keeping pace with the increase in population in an area. For this reason, this research was carried out with the aim of analyzing the relationship between the provision of basic infrastructure and the quality of the living environment in informal areas within the scope of slum areas so that it is hoped that this can be used as input in plans to improve or improve the welfare of the people therein. The research method was carried out through literature reviews, questionnaires and observations in selected areas. The analytical methods used are supply-demand analysis & qualitative descriptive analysis to describe the existing basic infrastructure in the research area, quantitative descriptive analysis to calculate the environmental quality index, and RPearson correlation analysis to see the relationship between the provision of basic infrastructure and the quality of the environment in the area. the study area, namely RW 13 and RW 14, Sadang Serang Village, Bandung City. The results obtained are that there is a relationship between the basic infrastructure provision variable and the environmental quality variable with a very strong correlation and the direction of the correlation is in the same direction or positive.